Interactive local tone mapping operator with the support of graphics hardware - Roch, Benjamin; Artusi, Alessandro; Michael-Grigoriou, Despina; Chrysanthou, Yiorgos; Chalmers, Alan G. (My University, 2007)
The flexibility of current graphics hardware is still not enough to ensure the full implementation of an original complex algorithm such as a local tone mapping operator, which maintains the same quality performances as its original CPU implementation. Significant changes are often needed to the original CPU implementation in order to overcome many of the limitations of the current graphics hardware. As a result of this we often have reduced quality reproduction, and the frame rate of the GPU implementation is not always acceptable for real-time applications. In this paper, we show how to change the CPU implementation of a state of the art local tone mapping operator for accelerating the computation process to real time frame rates. We also present a modification of the luminance local adaptation computation, showing a simple but not yet exploited property of the Gaussian filter, allowing us to maintain the same quality appearance of the original tone mapping operator. Finally we test the hardware implementation on NVIDIA graphics cards on several images and as well as a video. We compare our hardware implementation with the corresponding CPU implementation and previous work.
Keywords: Complex algorithms; Computer graphics; Computer hardware; Mapping